Grassland plant and invertebrate species richness increases from mowing are mediated by impacts on soil chemistry - Gillespie, Mark A.K.; Buckley, Hannah L.; Condron, Leo; Wratten, Stephen D. (Basic and applied ecology, 2022)
Pasture and improved grasslands are commonly managed by a combination of artificial fertilisation and biomass removal, but a deeper understanding of how management options interact over the long-term are required to improve sustainability. Studies of multi-trophic responses to these options can provide important insights for biodiversity and soil management, particularly when they cover long time periods. In this study, we provide a novel perspective on long-term experimental field studies of grassland management by examining the direct and indirect effects of N fertilisation and mowing (with biomass retention and removal) on above-ground biodiversity, below-ground soil chemistry and their interactions. Our experimental treatments were applied annually from 1994 in medium to high soil fertility conditions on a non-native pastoral farm in New Zealand, and analysis of data to 2013 show that in general, plants and soil properties did not respond to N fertiliser treatments. In response to mowing regimes, soil properties exhibited subtle, but annually varying changes mostly related to biomass retention or removal, and plant richness was consistently higher under all mowing treatments. The management regime with the greatest gains in diversity also depended on year of study. We further analysed the indirect effects of mowing treatments on plant and arthropod richness via soil properties using structural equation modelling, and found that the impact of mowing is likely to be mediated by soil chemistry changes. In particular, the direct positive impact of mowing on plant richness may be offset by changes to soil properties, depending on whether biomass is retained or removed. We suggest that management regime effects on soil chemistry may limit plant composition changes to those species able to take advantage of altered conditions. These findings suggest that management to improve grassland diversity and soil conditions should consider the abiotic history and conditions of the site.